(untitled) (El Hilo de la Fabula, 2023)
Thoughts on concepts such as “transculturation”, “cultural heterogeneity”, “hybridity”, “post-occidentalism” and "Latin American geoculture” in the light of contributions brought about by new trends in Comparative Literature and by the transcultural landscapes that have been remapping Latin America’s cartography.